Germination of Lactuca sativa L. Seeds after storage under different environments - Elsy, Anak Julian (Universiti Malaysia Sarawak, UNIMAS, 2013)
A study was conducted to evaluate the effect of different temperatures on for the storage of Lactuca sativa L. seeds. Seeds with 8.75% of moisture content and 59.0% of germination were desiccated with silica gel for 24 hours, and than placed in four different environments: ambient room (28-30˚C; 70-80% RH), refrigerator (3-5˚C; 42% RH), freezer (-4-0˚C; 30-35% RH) and incubator (35-38˚C; 40% RH) for 15 days. Seed stored in refrigerator (3-5˚C; 42% RH) gave high moisture content and the highest germination of 6.16% and 44.0% respectively. Regression analysis indicated the seeds stored in refrigerator (3-5˚C; 42% RH) maintained its germinability up to 109 days. Results showed that storage in refrigerator (3-5˚C; 42% RH) was a suitable condition for L. sativa seeds, before used as planting materials.